Effects of Individual Differences on Applicant Perceptions of an Operational Assessment Center. (December 2014) - Merkulova, Natalia; Melchers, Klaus G.; Kleinmann, Martin; Annen, Hubert; Tresch, Tibor Szvircsev
<x xml:space="preserve">Abstract</x> Knowing to what extent applicant reactions are related to stable individual differences and not only to characteristics of a selection procedure is important for the design and administration of the selection procedure and for dealing with applicants. The aim of this study was to explore relationships between individual differences (Big Five, core self‐evaluations, trait affectivity, and general mental ability) and applicants' perceptions of an operational assessment center (AC). Data from 294 applicants revealed that individual difference variables explained significant variance in their perceptions of the AC, even after controlling for self‐rated and actual performance. Based on these results, the nature of the applicant pool should be considered for designing selection procedures, dealing with applicants, and for research purposes.